2018
DOI: 10.18488/journal.1.2018.811.1005.1016
|View full text |Cite
|
Sign up to set email alerts
|

Stratified Property Management: Islamic Aspect

Abstract: Contribution/Originality: This study contributes in the existing literature in focusing on some of the views on management from the Islamic perspective which can be adapted in the management of multi storey development in Malaysia. However, there has been no direct principle that demonstrates management of stratified properties from the Islamic perspective. 1. INTRODUCTION In Malaysia, various activities are involved in stratified property management. Among these activities are obtaining and maintaining of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Students have the luxury to choose based on the comparison and reviews made by the alumni. Wadhwa (2016)and Mohamad and Hussein (2018). Meyer (2018) also highlighted that the decision-making by students will be based on their purpose and intention.…”
Section: Students' Decision Makingmentioning
confidence: 99%
“…Students have the luxury to choose based on the comparison and reviews made by the alumni. Wadhwa (2016)and Mohamad and Hussein (2018). Meyer (2018) also highlighted that the decision-making by students will be based on their purpose and intention.…”
Section: Students' Decision Makingmentioning
confidence: 99%
“…However, despite being established with the aim of reaching out to poor people, many MFIs end up serving the upper segment of the poor (i.e., the relatively better off segment of the poor), better than the lower segment of the poor (i.e., the poorest poor). Hence, although microfinance offers an effective means of reducing poverty, it may not necessarily address the problem of extreme poverty (Mosley, 2001;Mohamad & Hussein 2018). Evidence from Bolivia revealed that MFIs have been effective in reaching the poor, but not the poorest.…”
Section: Review Of the Literaturementioning
confidence: 99%